A Pre-Post Study on the Appropriateness and Effectiveness of a Web- and Text Messaging-Based Intervention to Reduce Problem Drinking in Emerging Adults - Haug, Severin; Schaub, Michael P; Venzin, Vigeli; Meyer, Christian; John, Ulrich; Gmel, Gerhard (JMIR Publications, 2013)
BackgroundProblem drinking, particularly risky single-occasion drinking (RSOD), also called "binge drinking", is widespread among adolescents and young adults in most Western countries. Few studies have tested the effectiveness of interventions to reduce RSOD in young people with heterogeneous and particularly lower educational background. ObjectiveTo test the appropriateness and initial effectiveness of a combined, individually tailored Web- and text messaging (SMS)-based intervention program to reduce problem drinking in vocational school students. MethodsThe fully automated program provided: (1) online feedback about an individual's drinking pattern compared to the drinking norms of an age- and gender-specific reference group, and (2) recurrent individualized SMS messages over a time period of 3 months. Generalized Estimating Equation (GEE) analyses were used to investigate the longitudinal courses of the following outcomes over the study period of 3 months: RSOD, alcohol-related problems, mean number of standard drinks per week, and maximum number of standard drinks on an occasion. ResultsThe program was tested in 36 school classes at 7 vocational schools in Switzerland. Regardless of their drinking behavior, 477 vocational school students who owned a mobile phone were invited to participate in the program. Of these, 364 (76.3%) participated in the program. During the intervention period, 23 out of 364 (6.3%) persons unsubscribed from participating in the program. The GEE analyses revealed decreases in the percentage of persons with RSOD from baseline (75.5%, 210/278) to follow-up assessment (67.6%, 188/278, P<.001), in the percentage of persons with alcohol-related problems (20.4%, 57/280 to 14.3%, 40/280, P=.009), and in the mean number of standard drinks per week: 13.4 (SD 15.3) to 11.3 (SD 14.0), P=.002. They also revealed a trend toward a decrease in the mean of the maximum number of drinks consumed on an occasion: 11.3 (SD 10.3) to 10.5 (SD 10.3), P=.08. ConclusionsThe results show high acceptance and promising effectiveness of this interventional approach, which could be easily and economically implemented within school classes.